THE INFLUENCE OF BPJS HEARING AID POLICY IMPLEMENTATION ON THE PATIENT ACCEPTANCE RATE AT CV POWER HEARING BALI - Azwar, Muhammad; Rusnita; Agustina, Christin; Munadhir; Zainuddin; Widiastuty, Lilis (Homes Journal = Hospital Management Studies Journal, 2025)
Background: One of the services covered by BPJS Kesehatan is the provision of hearing aids for patients with hearing impairments. Hearing aids play an important role in improving patients' quality of life in terms of communication, social interaction, and productivity. Objective: This study aims to analyze the effect of the implementation of the BPJS hearing aid policy on the level of patient acceptance.. Method: This research is quantitative with an analytical observational design. The sample consists of BPJS Kesehatan users who visited CV Power Hearing Bali and met the research criteria, totaling 30 individuals, selected using a total sampling technique. Data was collected using a Likert-scale questionnaire for all research variables. The collected data was then analyzed using the chi-square statistical test. Result: The study results indicate that the service received variable has a significance value (p-value = 0.007), waiting time (p-value = 0.048), and satisfaction level (p-value = 0.007). Conclusion: There is an influence of the implementation of the BPJS hearing aid policy on the level of patient acceptance at CV Power Hearing Bali.